1986
DOI: 10.1200/jco.1986.4.5.789
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous infusion of high doses of liposomes containing NSC 251635, a water-insoluble cytostatic agent. A pilot study with pharmacokinetic data.

Abstract: In patients with resistant malignant tumors, we performed a pilot trial of intravenous infusion of a water-insoluble cytostatic agent, NSC 251635, entrapped in large volumes of liposomes made of egg yolk lecithin, cholesterol, and stearylamine (4:3:1). Forty liposome infusions were given to 14 patients in 38 courses. The volume of liposomes (20 mg of lipids/mL) varied from 205 to 1,000 mL or 124 to 617 mL/m2 of body surface, and amounts of NSC 251635 varied from 82 to 456 mg/m2. Three patients received repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…These studies attest to the general safety of intravenous liposomes, as 4 liposomal drugs entrapping doxorubicin (Doxil), daunorubicin (DaunoXome), and amphotericin B (Abelcet and Ambisome) are already licensed in several countries and many others are in advanced clinical trials. 1 Nevertheless, some of the studies [2][3][4][5][6][7][8][9] have also revealed a hypersensitivity reaction to liposomes that develops immediately after the start of infusion and includes symptoms of cardiopulmonary distress, such as dyspnea, tachypnea, tachycardia, hypotension and hypertension, chest pain, and back pain. Unlike IgE-mediated (type I) allergy, the reaction to liposomes arises at first exposure to the drug without prior sensitization, and the symptoms usually lessen or disappear on later treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies attest to the general safety of intravenous liposomes, as 4 liposomal drugs entrapping doxorubicin (Doxil), daunorubicin (DaunoXome), and amphotericin B (Abelcet and Ambisome) are already licensed in several countries and many others are in advanced clinical trials. 1 Nevertheless, some of the studies [2][3][4][5][6][7][8][9] have also revealed a hypersensitivity reaction to liposomes that develops immediately after the start of infusion and includes symptoms of cardiopulmonary distress, such as dyspnea, tachypnea, tachycardia, hypotension and hypertension, chest pain, and back pain. Unlike IgE-mediated (type I) allergy, the reaction to liposomes arises at first exposure to the drug without prior sensitization, and the symptoms usually lessen or disappear on later treatments.…”
mentioning
confidence: 99%
“…[11][12][13] Nevertheless, complement activation has not been implicated previously in the abovedescribed clinical reactions. [2][3][4][5][6][7][8][9] In an effort to test the hypothesis that complement activation plays a causal role in the cardiopulmonary reaction to intravenous liposomes, we extended here an earlier report from our laboratory on liposome-induced anaphylactoid reaction in miniature pigs. 14 It was suggested in that study that the reaction was due to complement activation; however, direct, conclusive evidence regarding the causal role of complement was not available.…”
mentioning
confidence: 99%
“…For example, patients with resistant malignant tumors received 40 intravenous infusions of egg yolk lecithin-based liposomes entrapping a water-insoluble cytostatic agent. But while liposome therapy was very well tolerated, no objective regression of the tumors was observed-although the presence of the drug in the blood was prolonged for 120 hours after its administration (Sculier et al 1986). …”
Section: Liposomes Based On Egg Phospholipids Used In Pharmaceutics Amentioning
confidence: 96%
“…These mutations disrupt intrachain disulfide bridges, thereby perturbing the higher order structure of FH. This leads in turn to a profound selective block in secretion of the FH (12). On the other hand, recent studies showed hyperactivation of the alternative C pathway in neuropsychiatric disorders like schizophrenia: single nucleotide polymorphisms (SNPs) of gene encoding FH was found, CFH rs424535 (2783-526T > A) SNP was positively associated with schizophrenia.…”
Section: Fh Deficiency In Diseasesmentioning
confidence: 99%